A novel humanized mouse lacking murine P450 oxidoreductase for studying human drug metabolism - Mercedes Barzi; Francis P. Pankowicz; Barry Zorman; Xing Liu; Xavier Legras; Diane Yang; Malgorzata Borowiak; Beatrice Bissig-Choisat; Pavel Sumazin; Feng Li; Karl-Dimiter Bissig (Nature Communications, 2017)
Human liver chimeric mice are increasingly used for drug testing in preclinical development, but express residual murine p450 cytochromes. Here the authors generate mice lacking the Por gene in the liver, and show that human cytochrome metabolism is used following repopulation with human hepatocytes.